Aplikasi Sunnah Terhadap Garis Panduan Hukuman Rotan di Kementerian Pendidikan Malaysia - Siti Amalina Ahmad Khairundin; Mumtazah Narowi; Noor Fadhzana Mohd Noor; Hafiza Ab Hamid (USIM Press, 2024)
Vol 6. No. 1 (June 2021)